Cardiac emergencies in neonates and young infants - Nasib Kabbani; Mohamed S Kabbani; Hayan Al Taweel (Avicenna Journal of Medicine, 2017)
Cardiac emergencies in children are not infrequent. Early recognition and management are essential to save life and prevent any comorbidity. The presentation of cardiac emergencies and etiologies is variable depending on the age of child at the time of presentation and type of cardiac lesion. Cyanotic and noncyanotic congenital heart diseases are the main causes in neonates and infants. Acquired heart diseases and dysrhythmia are more common causes for cardiac emergencies in toddler and childhood. In this review, we discuss the most common causes for cardiac emergencies in neonates and young infants highlighting important points in the presentation and management that are essential for early recognition and timely management of infants presenting with these conditions.